Kombinasi Metode ARAS dan ENTROPY dalam Pemilihan Peserta Lomba Cerdas Cermat Tingkat Kabupaten - Lira Arum Kusumaning Thyas; Intan Meutia Sari (Journal of Informatics Management and Information Technology, 2025)
Decision Support System (SPK) is one of the systems that can help someone in making an accurate decision and can be right on target. Many problems can be solved using SPK. Decision Support Systems (DSS) are usually used to support a problem or for an opportunity. Decision Support System applications are usually used in making a decision. The additive ratio assessment method (ARAS) is a method used for ranking criteria, and entropy is a method that can be used in finding weights.